PENGARUH TENAGA KERJA, INFRASTRUKTUR, PENDAPATAN PERKAPITA DAN INVESTASI INDUSTRI DI KABUPATEN MERAUKE PERIODE TAHUN 2001-2017 - Romualdus Turu Putra Maro Djanggo; Marthen A I Nahumury (Musamus Journal of Economics Development, 2019)
The research aims to analyse whether the labour, infrastructure and Percapita income factors influence industrial investments in Merauke District in 2001-2017. The data used in this study is secondary data. The method of collecting data using secondary data from the official data is issued by the Department of Migration and Employment of Merauke District and the official data from the Central Statistics agency of Merauke District. For data processing is done using SPSS 21 program. The results of this research show that labor variables, infrastructure, and per capita income simultaneously affect the value of industrial investment. The result of the coefficient of determination (RÃ‚Â²) 25.6% showed that labor, infrastructure, and per capita income variables had no significant effect on increasing industrial investments. The results of this study also showed that the infrastructure variables were influential for the change in the value of industrial investments in Merauke district but the influence gained only on the level of 10% of its siknification. Keywords: Labour, infrastructure, investment value